Systemic Risk and the European Banking Sector - Nicola Borri; Marianna Caccavaio; Giorgio Di Giorgio; Alberto Maria Sorrentino (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2012)
Systemic risk is the risk of a collapse of the entire financial system, typically triggered by the default of one, or more, large and interconnected financial institutions. In this paper we estimate the systemic risk contribution of each financial institution in a large sample of European banks. We follow a recent methodology first proposed by Adrian and Brunnermeier (2011) based on the CoVaR and find that size is a predictor of a bank contribution to systemic risk, but it is not the only one. Leverage is important as well. Also, banks that have their headquarters in countries with a more concentrated banking system tend to contribute more to European wide systemic risk, even after controlling for their size. Therefore, any financial regulation designed only to curb banks' size would not completely eliminate systemic risk. On average, balance sheet variables are very weak predictors of banks' contribution to systemic risk, if compared to market based variables. Accounting rules provide enough degrees of freedom to make balance sheet less informative than market prices. As a result, measures of risk based on higher frequency market prices are more likely to anticipate systemic risk.
Keywords: G01; G18; G21; G32; 330; Systemic Risk; SIFIs; European Banking System; CoVaR